Borders and Pathways : Essays on Syrian Economic Development and Migrant Integration - Zalfou, Rami (2025)
Over the past century, Syria and the broader Middle East and North Africa (MENA) region have undergone profound demographic and economic transformations, yet they remain marked by deep regional, ethnic, and gender-based inequalities. These divisions have shaped development trajectories and contributed to social fragmentation, while successive waves of migration carried these dynamics abroad, from Ottoman-era migration to the Americas to the mass displacement of the Syrian civil war. Despite their importance, the long-run roots of Syrian inequality and the integration of Syrian and MENA migrants remain underexplored in the empirical social sciences. This dissertation addresses these gaps by analysing the historical determinants of development within Syria and the economic and social integration of Syrian and Middle Eastern migrants in host societies. The dissertation consists of four papers that combine economic history, demographic economics, and migration studies. Two focus on Syria, examining the long-term impact of historical statelessness on regional inequality and the drivers of ethnic and religious gaps in female labour force participation. The other two analyse migrant integration: the labour market outcomes of Ottoman migrants and their descendants in the United States during the early twentieth century, and the home-leaving behaviour of MENA-origin youth in contemporary Sweden. By linking historical and contemporary cases and applying methods ranging from spatial regression discontinuity and decomposition techniques to longitudinal analysis of census and register data, the dissertation provides novel quantitative evidence from contexts often overlooked in existing scholarship. The findings from Syria show that historical legacies and structural inequalities have enduring effects on development and gender outcomes. Regions historically beyond Ottoman state control remain disadvantaged in income, education, and infrastructure, with settlement patterns transmitting these gaps over time. Ethnic and religious disparities in women’s labour force participation are similarly rooted in structural conditions such as economic development, demographics, and access to public sector employment, rather than cultural norms alone. In host societies, integration unfolds differently across contexts and generations. Ottoman migrants initially faced earnings penalties despite occupational prestige, but their children achieved rapid upward mobility through education and occupational advancement. In contemporary Sweden, however, MENA-origin youth display persistent gaps in social integration: they leave the parental home later than natives, with women especially likely to remain at home or exit through marriage, and neighbourhood context strongly shaping outcomes.
Keywords: Syria; Economic Development; Migrant Integration